Psychological Profile of a 26-Year-Old Individual with Autism Spectrum Disorder in an Inclusive School Setting - Aisya Laila Delima; Nanda Audia Vrisaba (International Conference on Psychology and Education (ICPE), 2025)
This case study examines the psychological profile of a 26-year-old individual with Autism Spectrum Disorder (ASD) enrolled in Galuh Handayani School, an inclusive educational institution in Surabaya that accommodates both children and adults with special needs. The subject, JRA, continues to receive education and therapy in this setting due to persistent challenges in adaptive functioning, communication, and academic skills. This unique context—an adult still participating in a school-based inclusive program—reflects the scarcity of structured services for adolescents and adults with ASD in East Java. Data were collected through qualitative methods, including interviews, observations, and document analysis, and ASD characteristics were described according to the DSM-5 criteria. Results indicate that the subject demonstrates limited verbal communication, repetitive behaviors, and difficulties in social interaction and emotional regulation, while showing strengths in visual-motor skills, discipline, and adherence to routines. Interventions, including behavioral and occupational therapies, have contributed to improvements in compliance and emotional regulation, though communication remains the primary challenge. The findings underscore the importance of individualized, interest-based, and collaborative interventions in inclusive educational settings to support the development and adaptive functioning of individuals with ASD across the lifespan.